A Rare Case of Intraosseous Fibrolipoma of the Mandible: Diagnosis and Treatment. (5th April 2015) - Castellani, Andrea; Bocchialini, Gabriele; Ferrari, Luca
Abstract : Lipomas are common soft tissue tumors. Intraosseous lipoma is a rare lesion that constitutes not more than 0.1% of bone tumors. It can occur anywhere in the body and there have only been a few cases found in the mandible. Intraosseous fibrolipoma of the jaw is an uncommon histological variant of the classic lipoma and to the best of our knowledge only one case has previously been reported in the literature. The cause of this lesion is uncertain. Clinically the lesion is generally asymptomatic and its radiographic feature is a well-defined radiolucency. Surgery is the treatment of choice. We present a case of an intraosseous fibrolipoma in the right mandibular ramus in a 25-year-old female.